Predictors of health-related quality of life in stroke patients after neurological inpatient rehabilitation: a prospective study - Katona, Mirjam; Schmidt, Ralf; Schupp, Wilfried; Grässel, Elmar (Health and Quality of Life Outcomes, 2015)
The goal of the study was to investigate the long-term course of health-related quality of life (HRQoL) in stroke survivors during and up to 2.5 years after inpatient neurological rehabilitation and to identify predictors of HRQoL.HRQoL was determined in 152 stroke survivors in a single-centre prospective cohort study at four time points: upon admission to inpatient rehabilitation, at discharge, and one and 2.5 years after discharge. Their HRQoL was determined by administering the EQ-5D at all four measurement points. During inpatient rehabilitation, the SF-36 was administered in addition to the EQ-5D. Predictors were identified through multiple regression analysis.During inpatient rehabilitation, the "European Index" of the EQ-5D rose significantly (p < 0.001) from 45.4 to 66.7. The change in HRQoL on the SF-36 was convergent. The HRQoL of the stroke patients living at home remained at the same level for 2.5 years following discharge. In the multiple regression analysis, the EQ-5D Index at discharge (p = 0.049), the risk of falls as defined by Runge and Rehfeld (p = 0.001), and the change in emotional quality of life on the SF-36 during inpatient rehabilitation (p = 0.048) predicted HRQoL 2.5 years following discharge.On the basis of our results, we conclude that the long-term health-related quality of life of stroke survivors can be positively influenced by reducing the risk of falls and improving emotional well-being during neurological inpatient rehabilitation.
EVALuna2:23690